New Green Polymeric Composites Based on Hemp and Natural Rubber Processed by Electron Beam Irradiation - Maria-Daniela Stelescu; Elena Manaila; Gabriela Craciun; Maria Dumitrascu (The Scientific World Journal)
A new polymeric composite based on natural rubber reinforced with hemp has been processed by electron beam irradiation and characterized by several methods. The mechanical characteristics: gel fraction, crosslink density, water uptake, swelling parameters, and FTIR of natural rubber/hemp fiber composites have been investigated as a function of the hemp content and absorbed dose. Physical and mechanical properties present a significant improvement as a result of adding hemp fibres in blends. Our experiments showed that the hemp fibers have a reinforcing effect on natural rubber similar to mineral fillers (chalk, carbon black, silica). The crosslinking rates of samples, measured using the Flory-Rehner equation, increase as a result of the amount of hemp in blends and the electron beam irradiation dose increasing. The swelling parameters of samples significantly depend on the amount of hemp in blends, because the latter have hydrophilic characteristics.